Pengaruh Kepadatan Populasi dan Dosis Pupuk NPK terhadap Pertumbuhan dan Produktifitas Bawang Merah (Allium ascalonicum L.) dalam Polibag - ., Saliman; Furoidah, Nanik (JURNAL AGROPLANT, 2022)
This research was conducted from 24 September to 5 December 2020, in Pancakarya Village, Ajung District, Jember Regency, East Java. This study used  a 3 x 3 factorial pattern with a randomized block design (RBD) and was repeated three times. The first factor is population (J) consisting of population 2 (J1), population 3 (J2) and population 4 (J3), the second factor is the dose (D) consisting of 30gram (D1), 35gram (D2), 40gram (D3) . The collected data were analyzed using variance (ANOVA), if it was significantly different, then continued with the 5% Duncan test. The purpose of this study was to describe the population size in the cultivation of shallot plants in polybags and to describe the correct dosage of NPK fertilizer for shallot growth in polybags. The results showed that the treatment population (J), on the growth of shallots was significantly different to the increase in plant height, but the population treatment (J), the dose (D) on the growth and productivity of shallots did not give a significant difference to the number of tillers, wet weight, weight. dry weight and harves indexs.